2022
DOI: 10.1111/jam.15326
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi species improve the fatty acids profile and nutrients status of soybean cultivars grown under drought stress

Abstract: Aims:To investigate the effects of arbuscular mycorrhizal fungi (AMF) species on the absorption and distribution of mineral nutrients in soybean cultivars under drought stress, an experiment was carried out through a factorial method in the form of randomized complete blocks with six replicates in 2020. Methods and Results:Experimental factors include: drought stress at three irrigation levels (well-watered [WW], medium stress [MS] and severe stress [SS], i.e., 100%, 70% and 40% FC), soybean cultivars at two l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…AMF colonization improves resource efficiency, fatty acid profile, and yield stability, lowering the production risks associated with crops grown under drought stress conditions. It was decided that AMF colonization should be used to make drought stress less bad [ 43 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…AMF colonization improves resource efficiency, fatty acid profile, and yield stability, lowering the production risks associated with crops grown under drought stress conditions. It was decided that AMF colonization should be used to make drought stress less bad [ 43 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In response, host plants provide to the AMF with sugars that they would otherwise be unable to synthesise as chemoheterotrophic organisms [ 38 , 39 ]. The AMF are also recognized as plant stress alleviators [ [39] , [40] , [41] ]. For abiotic stresses, the AMF adaptation mechanisms are mostly correlated to enhanced mineral nutrition, ion uptake regulation, gene functioning and osmolytes, phytohormones and antioxidants biosynthesis [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, AMF increased apple tree drought resistance by regulating MAPK pathway genes (Huang et al, 2020). AMF is a useful tool for increasing plant nutrient uptake under drought stress conditions (Lotfabadi et al, 2022). Gao et al (2020) reported that dopamine promoted AMF symbiosis by increasing carbohydrate content, and the synergistic effect of dopamine and AMF enhanced apple tree salt resistance.…”
mentioning
confidence: 99%